Karakter Siswa Pada Pembelajaran Matematika di Sekolah Dasar Swasta Full Day School - Siregar, Nurdiana; Sundari, Dhea; Bakri, Aprilia (AR-RIAYAH: Jurnal Pendidikan Dasar, 2019)
This study aims to: a) describe the character of students in mathematics learning in a full day elementary school (SDS), b) find out the supporting and inhibiting factors in the formation and strengthening of character in mathematics learning at SDS full day school. This study used qualitative research methods. This research was conducted at SDS IT Siti Hajar. The technique of collecting data is by observation and interview. Data analysis techniques are data reduction, data display, and conclusions. The results showed that 1) the character of students in mathematics learning included religion, honesty, independence, tolerance, hard work, curiosity and responsibility 2) supporting factors for planting characters in mathematics learning include mathematics teacher figures, informal learning climate or not rigid, and learning methods that vary while the inhibiting factors cannot be implemented strict class rules in the form of punishment